Use Citrus aurantium plant as bio-indicator of air pollution in Baghdad city - AlObaidy, Wafaa Abdulrahman; Rabee, Adel Mashaan (Iraqi Journal of Science, 2018)
The current study was conducted to demonstrate the effects of air pollution on different biochemical parameters in Citrus aurantium plant and calculation the Air Pollution Tolerance Index (APTI). Five sites were selected to collect plant leaves, four of them within the city of Baghdad, namely Al-Jadriya, Al-Andlous, Al-Doura and close to the private generators to represent the urban areas and Abu Ghraib site to represent the rural area. Seasonal samples were collected for the period from October 2016 to June 2017. Eleven biochemical parameters total chlorophyll, ascorbic acid, leaf extract pH, relative water content, total nitrogen, total protein content, total sugar content, proline, electrical conductivity, cadmium and lead. The results of Citrus plant showed high chlorophyll concentration and ascorbic acid content in private generator site reached to (10.620 mg/g and 0.403 mg/g) respectively. While relative water content recorded high concentration (57.563 %) at Al-Jadriya site. pH recorded high value (6.358) at Al-Doura site. In addition, values of APTI of the Citrus plant were calculated to determine the sensitivity of the plant to air pollution. Highest value of APTI (6.23) was recorded at Al-Jadriya site, while lowest value of APTI (5.03) was recorded at Al-Andlous site. The results of present study revealed that Citrus aurantium is sensitive to air pollution and can be used as bio-indicator under pollution stress.